Interaction potential of the endothelin: a receptor antagonist atrasentan with drug transporters and drug-metabolising enzymes assessed in vitro - Weiß, Johanna; Haefeli, Walter E. (Cancer chemotherapy and pharmacology, 2011)
Atrasentan is a highly potent and selective endothelin receptor A (ETA) antagonist under development for the treatment of prostate cancer. Only little data exist on its interaction with drug-metabolising enzymes and drug transporters possibly influencing its safety and effectiveness. Our study evaluated whether atrasentan can induce the expression of relevant human drug transporters and cytochrome P450 isozymes (CYPs), whether it retains its efficiency in multidrug resistant cell lines, and whether it inhibits P-glycoprotein (P-gp) and breast cancer resistance protein (BCRP).